2010
DOI: 10.1007/s11127-010-9754-y
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering and the state

Abstract: Volunteering, Voluntary labor supply, Private provision of public goods, Public social expenditure, Political consensus, Democratization, H41, H44, H31, J22, I38, H11, D30, D64,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…One exception to this is a recent study that combines individual data from the World Values Survey with macroeconomic data from the OECD [11]. The data cover 24 OECD countries for the period 1981-2000 and contain information on individual participation in voluntary work as well as on countries' public social expenditure as a percentage of GDP.…”
Section: Studies Using Regional or Cross-country Variation In Public mentioning
confidence: 99%
“…One exception to this is a recent study that combines individual data from the World Values Survey with macroeconomic data from the OECD [11]. The data cover 24 OECD countries for the period 1981-2000 and contain information on individual participation in voluntary work as well as on countries' public social expenditure as a percentage of GDP.…”
Section: Studies Using Regional or Cross-country Variation In Public mentioning
confidence: 99%
“…From the macro perspective, gender differences in leisure participation are affected by the national expenditure on welfare, and by the level of the GDP (Van Ingen and Van der Meer 2011; Van Tuyckom 2011): that is, an increase in these factors reduces the gender gap. Regarding volunteering, the likelihood of volunteering is also influenced by other macro variables such as the extent of democratisation in the country, the extent of support for individuals mandated in government policies and the country's economic stability (Hackl, Halla and Pruckner 2012). However, Hackl, Halla and Pruckner (2012) also found that an increase in these factors, including welfare expenditure, actually reduces the likelihood of participating in leisure activities, especially among women, and increases inequality.…”
Section: The Current Studymentioning
confidence: 99%
“…However, the decision to volunteer might depend more strongly on macroeconomic factors than on individual, social, or geographic variables (Amin ; Atkinson, Buck, and Kintrea ; Hastings ; New Economics Foundation ). An important stream of research explores how a change in the size of the welfare state influences the decision to volunteer (e.g., Brooks , ; Hackl, Halla, and Pruckner ; Khanna and Sandler ; Van Oorschot and Arts 2005). These studies focus either on the entire population or on specific age groups (young people and retired people).…”
Section: Public Spending and Volunteering By Employed Individualsmentioning
confidence: 99%
“…At an aggregate population level, the evidence is mixed. Hackl, Halla, and Pruckner () found evidence for a crowding‐out effect because of an increase of the welfare state, while Van Oorschot and Arts (2005) did not. Menchick and Weisbrod () showed that tax rates influence the opportunity costs of volunteering.…”
Section: Public Spending and Volunteering By Employed Individualsmentioning
confidence: 99%